Website Content Extraction Using Web Structure Analysis - Daraham, Nor Hayati (Universiti Teknologi Petronas, 2005)
The Web poses itself as the largest data repository ever available in the history of humankind. Major efforts have been made in order to provide efficient to relevant information within huge repository of data. Although several techniques have been developed to the problem of Web data extraction, their use is still not spread, mostly because of the need for high human intervention and the low quality of the extraction results. For this project a domain-oriented approach to Web data extraction and discuss it application to extracting news from Web Sites. It will use the abstraction method to identify important sections in a web document. The relevance information will be taken account and will be highlighted in order to develop a focused web content output. The fact-finding and data about the project are gathered from various sources such as internet, and books. The methodology used is a Waterfall Model that involves several phases which are Planning, Analysis, Design and Implementation. The result of this project is the display and review of web content extraction and how it being currently being developed which the goals is to give more usability and easiness toward web users.